Pleural effusion as an isolated finding in COVID-19 infection. (2020) - Hussein, Mousa; Haq, Irfan Ul; Hameed, Mansoor; Thomas, Merlin; Elarabi, Anam; Allingawi, Mona; Al-Bozom, Issam
Abstract: Common radiological findings of COVID -19 infection include bilateral ground-glass opacities in lower lobes with a peripheral distribution. Pleural effusion is considered a rare manifestation of COVID -19 infection. We present a 52 years old patient with a three-week history of right-sided pleuritic chest pain, fever, and dyspnea. Laboratory investigations revealed high C -reactive protein and ferritin levels and a positive COVID-polymerase chain reaction (PCR) from a nasopharyngeal swab. Chest X-ray and Computed tomography (CT) identified a moderate right-sided pleural effusion, which was exudative with mixed cellularity and high Lactate dehydrogenase (LDH). Histopathology of thoracoscopic pleural biopsy didn't reveal granulomas, malignancy, or any microbiological growth. We postulate that having ruled out any other cause the effusion was likely related to the Covid-19 infection. Our case highlights that COVID-19 can present with isolated pleural effusions, therefore it should be kept as an etiology of effusions especially if other possible causes have been ruled out.